Vietnam’s Ministry of Agriculture and Rural Development adopts CCAFS' outputs and inputs on its major climate-smart agriculture-related policies and programs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Through CCAFS outputs and capacity building activities, the key officials and staff of at least eight offices under the Ministry of Agriculture and Rural Development (MARD) enhanced their knowledge, skills, and favorable attitude towards climate-smart agriculture (CSA). This has enabled the mainstreaming of CCAFS outputs and inputs in the national policies (e.g. Resolution-120, Nationally Determined Contributions(NDC), UNFCCC-SBSTA submissions) and key programs (i.e., New Rural Development Program, National Adaptation Plan in Agriculture(NAPAg), Sustainable Agricultural Transformation, and the Rice Master Plan).